Serum magnesium levels in type 2 diabetes - Rao, Yeluri Seshagiri; V., Dharma Rao (International Journal of Research in Medical Sciences, 2016)
Background: Several studies undertaken in different parts of the world have shown that hypomagnesemia occur at an increased frequency among patients with type 2 diabetes compared with their counterparts without diabetes. As current data suggest adverse outcomes in association with hypomagnesemia, it is prudent to monitor magnesium routinely in this patient population and treat the condition whenever possible. Therefore, this study was undertaken to determine the serum magnesium levels in type 2 diabetes in this part of our country. Methods: A cross-sectional study was conducted in 100 subjects, 50 diabetics without complications (group I), 50 diabetics with complications (group II) and 100 normal healthy controls (group III). Blood sugar levels, magnesium, HbA1C (%), cholesterol and triglyceride level were measured. Results: Serum magnesium levels were found low in study group as compared to control group. A significant correlation between HbA1C and magnesium levels was seen. The patients with diabetic complications have significantly higher values of serum cholesterol and triglycerides. Conclusions: Hypomagnesemia in type 2 diabetes was associated with poor glycemic control and with increased frequency of long term complications.